Araceae of Mulu National Park. I. Four new species of Schismatoglottis (Araceae) - Wong, Sin Yeng; Boyce., Peter C.; Aisahtul, Wardi; Chai, Shong Kian (John Wiley & Sons Ltd, 2019)
Four new species of Schismatoglottis are described and illustrated from Mulu National Park in Malaysian Borneo: Schismatoglottis fossae (Patentinervia Clade), S. roseopedes and S. serratodentata (Calyptrata Clade) and S. pellucida (currently unplaced but likely in the Multinervia clade). A brief summary is provided of botanical exploration at Mulu, notably where pertinent to aroid botany.